Utilization of white rot fungi for textile dye decolourisation under alkaline condition and high salt concentration in solid medium - Ottoni, C. A. (2010)
A large amount of azo dyes are used for dyeing textiles. However, the dyes contaminate wastewaters and need to be treated. This is important because of the aesthetic, toxic and carcinogenic effects of the affected waters. Recently there has been an increase in interest in using white rot fungi (wrf) which degrade xenobiotic compounds including azo dyes. Wrf degrade lignin and others recalcitrant molecules using nonspecific extracellular enzymes. Four white rot fungi obtained from the Micoteca da Universidade do Minho (MUM) culture collection were used to screen for degradability capabilities. Reactice Black 5 (RB5) was selected in the present work because these dyes are most commonly used in the textile dyeing. Screening for RB5 decolourisation was carried out on solid medium in plates. Two wrf showed good growth and decolourisation abilities. These are now under study to determine which ligninolytic enzymes are produced.